ALIH KODE DAN CAMPUR KODE DALAM NOVEL RANAH TIGA WARNA KARYA AHMAD FUADI - Satriyani Satriyani; M. Nur Mustafa; Hermandra Hermandra (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRACTThis research is a study of code switching and mixed code contained in the Ranah Tiga Warna novel by Ahmad Fuadi. This research aimed to describe the pattern of code switching, the type of code switching, source language code mixing, and the type of code mixing in the Ranah Tiga Warna novel by Ahmad Fuadi. To analyze the pattern and the type of code switching used Auzar theory and Suwito. To analyze the type of code mixing used Suwito theory and Indra. The method used in this research is descriptive method, ie a method of research that attempted to describe as objectively as possible the state of the object to the fact that the study found, the reference framework decomposes the data that is qualitative research in the form of words and not in the form of numbers. Conclusion of this research is composed of a pattern of code switching code intralanguage aggregate 5 data and code switching patterns across languages aggregate 9 data. Types of code switching consists of the type of internal code switching aggregate 5 data and type of external code switching aggregate 9 data. Resources language mixing code source Minang language aggregate 22 data, Java language aggregate 5 data, Lampung language aggregate 1 data, Sunda language aggregate 9 data, the Jakarta dialect language aggregate 2 data , English language aggregate 34 data, Arabic language aggregate 12 data, French language aggregate 35 data, and Indian language aggregate 2 data. Type code mixed consists of three, which is into code mixed aggregate 36 data, out code mixed aggregate 75 data, and mix mixed code aggregate 5 data.Keywords: code switching, code mixing, and novel